The Role and Authority of The Civil Service Police Unit (Satpol PP) in The Tourism Sector in Banyumas Regency - Ixora Adhitama; Aditya Riza Dharmawan (Universitas Amikom Purwokerto, 2025)
Banyumas Regency is one of the strategic areas in Central Java Province that has a diverse range of tourism potential. In 2024, there were 94 tourist attractions recorded, with a total of 1,127,432 visitors, contributing to local revenue and providing an economic impact. Along with the increasing number of tourists and the complexity of tourism management, the need for supervision, security, and order has become increasingly important. This places the Civil Service Police Unit (Satpol PP) as a central element in the enforcement of local regulations and the maintenance of public order in tourist destinations. Based on Law Number 23 of 2014 and Government Regulation Number 16 of 2018, Satpol PP has the authority in non judicial regulation, investigation of regional regulation violations, administrative actions, and enforcement of public order. This study uses a normative juridical method with a legislative and conceptual approach to analyze the normative basis and the implementation of Satpol PP's authority in the management of tourism in Banyumas Regency. The study results indicate that the high number of tourist attractions and the increase in tourists create a need for special supervision by the Public Order Agency (Satpol PP). The limited number of personnel is a major obstacle to the optimal performance of Satpol PP's duties. Therefore, strengthening the role of Satpol PP, including the option of establishing a special unit for the tourism sector, becomes an important strategy to achieve safe, orderly, and sustainable tourism management in Banyumas Regency.